PHARMACOGNOSTIC AND PRELIMINARY PHYTOCHEMICAL ANALYSIS ON BENINCASA HISPIDA FRUIT - Nadhiya, K.; Haripriya, D.; Vijayalakshmi, K. (Asian Journal of Pharmaceutical and Clinical Research, 2014)
To study the plant drug formulation which has lots of secondary metabolites have medicinal property with fewer side effects and less expensive source materials. The present study was designed to investigate the Pharmacognostical as well as Preliminary Phytochemical studies on Benincasa hispida fruit. The present study highlights the parameters such as macroscopic, microscopic characters, physical evaluation, and powder analysis with chemical agents, Fluorescence analysis of powder sample and preliminary phytochemical studies. In the present study we have Phytochemicals from extracted dried fruit powder of Benincasa hispida in Ethyl acetate, Ethanol, Hydro alcohol and Aqueous. Microscopic analysis was done using Toluidine Blue staining reagent. Physical evaluation like ash value, extractive value and loss on drying, powder analysis with chemical agents and fluorescence analysis of powder sample were performed. Pharmacognostic study with Toluidine blue staining reagents shows Parenchyma, Vascular strand, Xylem, Phloem, ground tissue and crystals in transverse section of fruit. The preliminary phytochemical studies revealed the presence of carbohydrates, Phenols, alkaloids, glycosides, flavonoids, tannins and saponins. Physiochemical studies revealed the Total ash is 6.89percent, Acid insoluble ash 2.35percent, Water soluble ash 3.12percent, sulphated ash 5.42percent, water soluble extract value is 45.4percent, Hydro alcohol soluble extract value is 7.14, Ethanol soluble extract value is 12.58 and Ethyl acetate extract value is 6.6. Changes with chemical agents and fluorescence analysis are identified. This identity will be useful in identification of potent drug formulation. KEY WORDS Benincasa hispida, Macroscopic, Microscopic, Physiochemical and Phytochemical